Synthesis, Crystal and Supermolecular Structure of (Z)-4-({4-[1-(Hydroxyimino)ethyl]-phenylimino}(phenyl)methyl)-3-methyl-1-phenyl-1H-pyrazol-5(4H)-one - Dong, W.-K.; Yang, Y.-H.; Dong, X.-Y.; Zhao, M.-M.; Li, X. (Asian Journal of Chemistry, 2013)
The compound, (Z)-4-({4-[1-(hydroxyimino)ethyl]phenylimino}(phenyl)methyl)-3-methyl-1-phenyl-1H-pyrazol-5(4H)-one has been synthesized and characterized by elemental analyses, IR spectra and X-ray diffraction method. This compound is a potential tridentate ligand containing mono-oxime group. In the crystal structure, there are two crystallographically independent but chemically identical molecules (molecules A and B). There are two strong intramolecular N3-H3···O1 and N7-H7···O3 hydrogen bonds form six-membered S(6) ring motifs. Each molecule A interlinks two neighboring molecules B into a 1D infinite chain through six intermolecular O2-H2···N6, C29-H29A···O2, C35-H35···N4, O4-H4···N2, C4-H4A···O4 and C10-H10···N8 hydrogen bonds and each molecule B interlinks two neighboring molecules A into the other 1D infinite chain in the same way. Furthermore, the two dual chains are further stabilized by intermolecular C50-H50B···O1 hydrogen bonds to form an infinite 2D supramolecular network structure.